Miracles today : the supernatural work of God in the modern world - Keener, Craig S., 1960- (Grand Rapids, Michigan : : Baker Academic, a division of Baker Publishing Group, 2021)
"A leading New Testament scholar not only addresses common questions about miracles but also demonstrates that miraculous works of God have been part of the church's experience around the world since Christianity began and that they continue into the present"--
Includes bibliographical references (pages 239-284)
Keywords: Miracles